Use of discrete Wigner functions in the study of a hybrid dissipative system. (23rd August 2017) - Reboiro, M; Civitarese, O; Ramirez, R; Tielas, D
Abstract: The persistence of coherence in a hybrid dissipative system, which is composed of superconducting flux-qubits (SFQs) and an electron ensemble, is analyzed. Both the interactions between the electrons and the SFQs are taken into account. The time evolution of the hybrid system is discussed in terms of the discrete Wigner function of each subsystem and in terms of the entropic uncertainty relations. The inclusion of a linewidth, both for the electrons and the SFQs, influences the coherence of each subsystem and the pattern of spin squeezing of the corresponding steady state.